Costs associated with acute respiratory illness and select virus infections in hospitalized children, El Salvador and Panama, 2012–2013. Issue 2 (August 2019) - Jara, Jorge H.; Azziz-Baumgartner, Eduardo; De Leon, Tirza; Luciani, Kathia; Brizuela, Yarisa Sujey; Estripeaut, Dora; Castillo, Juan Miguel; Barahona, Alfredo; Corro, Mary; Cazares, Rafael; Vergara, Ofelina; Rauda, Rafael; et al.
Highlights: Median cost per severe acute respiratory illness (ARI) was US219–393. Median cost per severe ARI was equal to 43–79% of national health expenses per capita. Severe ARIs requiring intensive care cost 5–8 times more than those that did not. Caregivers bore approximately one fourth of costs of severe ARI. Severe ARI frequently resulted in lost work days and wages for caregivers. Abstract: Background and objectives: Although acute respiratory illness (ARI) is a leading cause of hospitalization among young children, few data are available about cost of hospitalization in middle-income countries. We estimated direct and indirect costs associated with severe ARI resulting in hospitalization among children aged <10 years in El Salvador and Panama through the societal perspective. Methods: During 2012 and 2013, we surveyed caregivers of children hospitalized with ARI about their direct medical (i.e., outpatient consultation, medications, hospital fees), non-medical (transportation, childcare), and indirect costs (lost wages) at discharge and 7 days after discharge. We multiplied subsidized hospital bed costs derived from administrative data by hospitalization days to estimate provider costs. Results: Overall, 638 children were enrolled with a median age of 12 months (IQR 6–23). Their median length of hospitalization was 4 days (IQR 3–6). In El Salvador, caregivers incurred a median of US38 (IQR 22–72) in direct and indirect costs per illness episode, while the median government-paid hospitalization cost was US118 (IQR 59–384) generating an overall societal cost of US219 (IQR 101–416) per severe ARI episode. In Panama, caregivers incurred a median of US75 (IQR 39–135) in direct and indirect costs, and the health-care system paid US280 (IQR 150–420) per hospitalization producing an overall societal cost of US393 (IQR 258–552). Conclusions: The cost of severe ARI to caregivers and the health care system was substantive. Our estimates will inform models to estimate national costs of severe ARI and cost-benefit of prevention and treatment strategies.